REPRODUCTIVE, BIOCHEMICAL, AND HORMONAL TRAITS OF LOCAL QUAIL IN RESPONSE TO DIETARY SUPPLEMENTATION OF DRIED GARLIC POWDER - Ismael, Lanja A.; M. Ameen, Edrees (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The study was conducted to find out the effect of dried garlic (Allium sativum) powder at different levels on the productive and reproductive performance of local quail. About ninety female local quail were used. The quails were divided into six groups (control, standard diet + 3% lipid, standard diet + 2% powder garlic, standard diet + 2% powder garlic + 3% lipid, standard diet + 4% powder garlic, and standard diet + 4% powder garlic + 3% lipid). A higher significance (p≤0.05) in egg weight (11.69 g/egg), feed intake (2977.13 g/week), hen day egg production (92.48 %), and egg mass (10.62) was recorded of quail eating (4% powder garlic). The results show the significant (p≤0.05) superiority of quails fed 4% of garlic powder in the internal egg characteristics such as egg albumen weight, yolk height, Haugh unit, and egg hardness. A significant (p≤0.05) improvement in the blood lipid profile in favor of quail birds fed on rations containing dried garlic powder, as the highest value for total cholesterol, triglycerides, LDL, and VLDL found in the treatment of birds fed on high lipids, while the highest values ​​of HDL were in the treatments of fed different levels of garlic powder. The highest levels of Ghrelin, T4, and LH, hormones were recorded for quail birds fed with 2% garlic powder. Birds fed on high lipid diet showed higher concentrations of leptin and growth hormone, while the higher value of FSH was seen in a 4% garlic supplemented diet. We conclude from the above that birds fed 4% dried garlic powder were superior in most productive and reproductive traits, compared to other treated birds.